2022
DOI: 10.7717/peerj.13677
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of light quality is an effective tool to regulate photosynthetic capacity and fruit antioxidant properties of Solanum lycopersicum L. cv. ‘Microtom’ in a controlled environment

Abstract: Light quality plays an essential role in setting plant structural and functional traits, including antioxidant compounds. This paper aimed to assess how manipulating the light spectrum during growth may regulate the photosynthetic activity and fruit bioactive compound synthesis in Solanum lycopersicum L. cv. ‘Microtom’ to improve plant physiological performance and fruit nutritional value. Plants were cultivated under three light quality regimes: red-green-blue LEDs (RGB), red-blue LEDs (RB) and white fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 83 publications
1
9
1
Order By: Relevance
“…Adding blue to a red light background increased leaf number and leaf area in several tomato cultivars and species (Hernández et al, 2016; Ouzounis et al, 2016), whereas another analysis (of young plants) showed that only dry weight partitioning to the leaf, compared to stem, was increased (Kalaitzoglou et al, 2021). For ‘Micro Tom’ in particular, in one case, a higher blue proportion resulted in increased SLA, not leaf number and area (Ke et al, 2022), in another case, a low leaf number and small leaf area (Vitale et al, 2022) – a discrepancy likely caused by different light recipes used (specifically, the quantities of green and far-red light). The variation in phenotypes observed are likely due to the large natural variation in tomato.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding blue to a red light background increased leaf number and leaf area in several tomato cultivars and species (Hernández et al, 2016; Ouzounis et al, 2016), whereas another analysis (of young plants) showed that only dry weight partitioning to the leaf, compared to stem, was increased (Kalaitzoglou et al, 2021). For ‘Micro Tom’ in particular, in one case, a higher blue proportion resulted in increased SLA, not leaf number and area (Ke et al, 2022), in another case, a low leaf number and small leaf area (Vitale et al, 2022) – a discrepancy likely caused by different light recipes used (specifically, the quantities of green and far-red light). The variation in phenotypes observed are likely due to the large natural variation in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato-specific blue light benefits include prevention of grey mold disease and reduction of intumescence injury (Imada et al, 2014; Retana-Cordero et al, 2022). In addition, blue light affects tomato nutritional quality (He et al, 2022; Ntagkas et al, 2020; Vitale et al, 2022; Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A significant area of focus in the field of tomato production is yield and fruit quality in response to light ( Vitale et al., 2022 ). Since major categories of secondary plant metabolites are present in tomato fruit ( Li et al., 2020 ), the rapid cycling MicroTom is an ideal candidate to study fruit quality in response to different abiotic factors.…”
Section: Microtom Fruit Pigments Are Normal In Tissue Culturementioning
confidence: 99%
“…Since major categories of secondary plant metabolites are present in tomato fruit ( Li et al., 2020 ), the rapid cycling MicroTom is an ideal candidate to study fruit quality in response to different abiotic factors. Although light quality can significantly impact the nutritional value of growth chamber produced MicroTom fruit by increasing antioxidant levels ( Vitale et al., 2022 ), it is unknown if the secondary metabolite activities of in vitro MicroTom fruit mimic their ex vitro counterparts. This represents an important area of focus for fruit production and quality in response to light, and a research area perfectly suited for the tissue culture approach.…”
Section: Microtom Fruit Pigments Are Normal In Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation